PENGARUH PELATIHAN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA DIREKTORAT KEPOLISIAN UDARA CABANG TANGERANG SELATAN - Hariyanto Hariyanto; Sutrisno Sutrisno (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The purpose of this study was to determine the effect of training and communication on employee performance at the South Tangerang Branch of the Air Police Directorate partially and simultaneously. The method used was quantitative. The sampling technique used the Slovin formula and obtained a sample of 87 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of this study are that training has a significant effect on employee performance with the regression equation Y = 14.117 + 0.637X1, a correlation coefficient value of 0.602 (strong), a determination coefficient of 36.2% and a hypothesis test obtained t count > t table or (6.948 > 1.988). Communication significantly influences employee performance, as shown in the regression equation Y = 13.188 + 0.645X2, with a correlation coefficient of 0.684 (strong), and a coefficient of determination of 46.8%. The hypothesis test yielded a calculated t-value > t-value (8.642 > 1.988). Training and communication simultaneously significantly influence employee performance, as shown in the regression equation Y = 6.928 + 0.346X1 + 0.477X2. The correlation coefficient was 0.737 (strong), with a coefficient of determination of 54.3%, while the remaining 45.7% was influenced by other variables. The hypothesis test yielded a calculated F-value > F-value (49.932 > 3.110).